Seni Gamelan Jawa Memiliki Peran Dalam Meningkatkan Pemahaman Tanda Bahaya Kehamilan - Yulifah, Rita (Malang Journal of Midwifery (MAJORY); Vol 2 No 1 (2020): MAJORY, 2020)
Pregnancy is a natural process, but on the way it does not rule out danger signs in pregnancy. Not all pregnant women and their families understand the danger signs of pregnancy. To increase the understanding of mothers and the public about the danger signs of pregnancy, researchers will develop the art of gamelan by including messages about pregnancy danger signs. The research design used was an experiment with a pretest-post test control group design. The research subjects were 60 pregnant women who were taken by simple random sampling and divided into the control group and the treatment group. Data were collected using a pregnancy danger sign questionnaire, then analyzed using an independent sample test. The results showed that before being given the treatment, 17 out of 30 pregnant women had an understanding in the sufficient category and after being given treatment using the art of gamelan 20 mothers had a good understanding. The results of the independent sample test showed that the Javanese gamelan art media was effective in increasing the mother's understanding of the danger signs of pregnancy (p value 0.001). Gamelan music containing danger signs lyrics can be used as a medium to convey messages about pregnancy danger signs to pregnant women and the public. By using the media of gamelan music, there is a tendency to be able to increase the understanding of pregnant women about the danger signs of pregnancy ranging from moderate to good categories. Keywords: Media, Gamelan Music, Understanding Pregnancy Hazard Signs